Iniciativas de segurança na medicação em hospitais do estado de Goiás - Sagawa, Marcella Rarumi (2019)
INTRODUCTION: Adverse events associated to the use of medications are a major concern addressed by studies conducted in several countries. Various initiatives have been implemented worldwide to increase medication safety. OBJECTIVE: To investigate initiatives to improve medication safety implemented by hospital institutions in Goiás. METHODOLOGY: Descriptive study carried out in six public hospitals using a semi-structured instrument, containing questions related to the characterization of institutions and 14 safety initiatives in the prescription of medication, nine in the storage, dispensing and distribution of medicines, 25 in the preparation and administration of medicines and two in the transition of care. The study was approved by the Research Ethics Committees of the participating institutions. RESULTS: All hospitals had a Patient Safety Center and anonymous incident notification system; three (50.0%) had quality certification. The average number of safety initiatives in the medication implemented was 8.5 in the prescription process; 8.6 in storage, dispensing and distribution; 16.1 in preparation and administration and 1.3 in the transition of care. Prescription process at all hospitals had drug standardization and information about institutions / patients and safety measures for prescribing potentially dangerous drugs. The standardization of the list of prohibited abbreviations was neither implemented nor planned in five hospitals. In the process of storage, dispensing and distribution of medicines, all hospitals had environmental safety measures and good storage practices in the central pharmacy, standardization of good practices for the separation of medicines, registration and notification of dispensing errors, availability of a pharmacist to review prescriptions, monitoring system and temperature control in specific refrigerators for the storage of thermolabile medicines, and care with storage in the care units. Four hospitals had a unit dose distribution system. All hospitals had a protocol for safe preparation and administration of medications; protocol with mandatory verification items before administration; standardization and verification of patient identification data; checking the prescription immediately after administration; standardization of equipment; return of remnants of medication in the same shift / day and medical records of drug therapy complications. Continuing education and the construction of standards and protocols were actions used to implement initiatives in all hospitals. To maintain the initiatives, hospitals used actions such as the periodic review and updating of institutional protocols (100.0%) and the sharing of incidents among professionals, without exposing those involved (83.3%). About the initiatives evaluation, 28 (56.0%) of the 50 initiatives were evaluated by outcome indicators by at least one of the hospitals. In general, hospitals were satisfied with the adherence of professionals to the initiatives. CONCLUSION: The study shows that hospitals comply with several national and international recommendations for promoting safety in medication processes. However, there is still a need for investments in important initiatives advocated for the prevention of incidents that can cause harm to patients during the medication process.